Multivariable calculus with mathematica - Gilbert, Robert P., 1932- (Boca Raton : Chapman & Hall/CRC Press, 2020)
"Multivariable Calculus with Mathematica is a textbook addressing the calculus of several variables. Instead of just using Mathematica to directly solve problems, the students are encouraged to learn the syntax and to write their own code to solve problems. This not only encourages scientific computing skills but at the same time stresses the complete understanding of the mathematics. Questions are provided at the end of the chapters to test the student's theoretical understanding of the mathematics, and there are also computer algebra questions which test the student's ability to apply their knowledge in non-trivial ways. Features Ensures that students are not just using the package to directly solve problems, but learning the syntax to write their own code to solve problems Suitable as a main textbook for a Calculus III course, and as a supplementary text for topics scientific computing, engineering, and mathematical physics Written in a style that engages the students' interest and encourages the understanding of the mathematical ideas"--
OCLC-licensed vendor bibliographic record.
Keywords: Calculus; MATHEMATICS / General; MATHEMATICS / Algebra / General; MATHEMATICS / Number Systems